Predictive Ability of Experiential Avoidance in Symptoms of Psychosomatic Disorders in Abused Women - Khatatbeh, Yahya Mubarak; Al-Saliti, Rawan Abdul Mahdi Neyef (Journal of Posthumanism, 2025)
Objectives: The study aimed to reveal the predictive ability of experiential avoidance and demographic variables (age group, marital status, and educational level) in symptoms of psychosomatic disorders in abused women. Methodology: The descriptive correlational method was used for its suitability to the objectives of the study. The study sample consisted of (267) abused women who visited the Family Accord House and the Jordanian Women's Union in Irbid city, during the period from 12/2/2024 to 2/5/2025. They were selected using the convenient method to ensure reaching the largest possible number of abused women without time or resource restrictions. Of them, (113) women visited the Family Accord House and (154) women visited the Jordanian Women's Union. They were selected using the convenient method. The experimental avoidance scale and symptoms of psychosomatic disorders were used to verify the study objectives. Results: The results revealed an average degree for both experimental avoidance and symptoms of psychosomatic disorders among abused women. The results also revealed that the variable involved in predicting the psychosomatic disorders scale is the experimental avoidance scale, which explained (3.3%) of the explained variance for the psychosomatic disorders scale, and the variance ratio for this variable was statistically significant at the significance level (α = 0.05). The variables of educational level, age, and social status were not included in the prediction of the psychosomatic disorders scale.